2018
DOI: 10.1007/s10897-018-0267-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Adolescence on Parents’ Perspectives of Testing and Discussing Inherited Cancer Predisposition

Abstract: Li-Fraumeni syndrome (LFS) is a highly penetrant cancer predisposition syndrome that may present with a first cancer before or during adolescence/young adulthood. Families offered LFS genetic testing for their children can inform our understanding of how the unique developmental context of adolescence influences parental perspectives about genetic testing and discussions of cancer risk. In this study, semi-structured interviews were conducted with 46 parents of children at risk for LFS to capture those perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…However, some children ultimately felt parents should make the decision . A recent study of 46 parents of children at risk of LFS acknowledged adolescent should take more responsibility of their health care decisions and knowledge of their risk may moderate risky health behaviours . Conversely, parents worried that testing during adolescents, an already emotional difficult time, may heighten negative emotions associated with testing .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some children ultimately felt parents should make the decision . A recent study of 46 parents of children at risk of LFS acknowledged adolescent should take more responsibility of their health care decisions and knowledge of their risk may moderate risky health behaviours . Conversely, parents worried that testing during adolescents, an already emotional difficult time, may heighten negative emotions associated with testing .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 46 parents of children at risk of LFS acknowledged adolescent should take more responsibility of their health care decisions and knowledge of their risk may moderate risky health behaviours . Conversely, parents worried that testing during adolescents, an already emotional difficult time, may heighten negative emotions associated with testing . Despite parental concerns, the majority of adolescents tested did not report being negative affected by the testing process …”
Section: Discussionmentioning
confidence: 99%
“…Such benefits included: the reduction of uncertainty and satisfying the need to know, [46][47][48][49][50] understanding the cause for a cancer diagnosis, 47,51 the ability to understand the risk to oneself and to family members, [46][47][48][49][50] and having the option to pursue ongoing surveillance. 46,47,49,50,52 Several studies reported the concern for negative psychosocial impact as a major challenge or risk to the election of TP53 genetic testing. Additional reasons for declining testing included: perceived lack of benefit of screening 49,50 and added emotional or logistical burden.…”
Section: Age Agnostic/across the Lifespanmentioning
confidence: 99%
“…Additional reasons for declining testing included: perceived lack of benefit of screening 49,50 and added emotional or logistical burden. 46,49,52,53 Both adolescents undergoing genetic testing and parents deciding to test their children expressed concern over privacy, insurance issues, and risk to employment. 46,48,50,51 To help clarify risks and benefits of undergoing testing, several studies suggested the use of developmentally appropriate decisionmaking aids during the genetic counseling process.…”
Section: Age Agnostic/across the Lifespanmentioning
confidence: 99%
“…Studies about long-term effect of surveillance in healthy carriers in hereditary kidney cancer families are needed. Additionally, further research is needed to understand the actual impact of genetic testing on young family members [63].…”
Section: Future Perspectivesmentioning
confidence: 99%